Excavations at Nemea III : the coins - Knapp, Robert C. (University of California Press, 2005)
Cover -- Contents -- Preface and Acknowledgements -- List of Illustrations -- Selected Bibliography and Abbreviations -- Specialized Terminology and Abbreviations -- Elevations, Grid References, and Measurements -- Part I. The Classical, Hellenistic, Roman Provinial, and Roman Coins -- Conspectus of Coins -- Introduction: Archaeonumismatics and Nemea -- Catalogue of Coins, Part I -- Part II. The Early Christian and Later Coin Finds from Nemea -- Introduction -- Catalogue of Coins, Part II -- Index of Subjects, Ancient Sources, and Modern Scholars -- Indices to the Catalogue -- Index of Inventoried Coins -- Plates.